2020
DOI: 10.1111/bjh.17169
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic lymphoma kinase (ALK)‐negative anaplastic large cell lymphoma with MYC rearrangement

Abstract: Anaplastic large-cell lymphoma (ALCL) can be further classified into anaplastic lymphoma kinase-positive (ALK +) and ALK-negative types. ALK-negative ALCL is indistinguishable from ALK + ALCL by morphology, but lacks ALK translocation or protein expression. Patients with ALK + ALCL have an overall better prognosis than patients with ALK-negative ALCL, in part because they are younger, but also likely due to biological factors because ALK-negative ALCL is a molecularly heterogeneous entity. 1,2 MYC is altered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Other IRF4 alterations, most commonly extra copies of IRF4, were seen in a wide variety of T-cell lymphoproliferative disorders, including cutaneous ALCL, and were mutually exclusive with cases harboring IRF4/DUSP22 translocations [10]. The effects of additional cytogenetic alterations on prognosis are unknown; rare cases of DUSP22 rearranged ALCLs demonstrating other alterations, one with concurrent TP63 rearrangement and another with concurrent MYC rearrangement, showed complete remission after chemotherapy although the patient with DUSP22 and MYC rearrangements died 53 months after diagnosis from an unknown cause [8,12]. There is no consensus on the optimal therapy for PCNSL, but treatment most often consists of high-dose methotrexate as part of multiagent chemotherapy, with or without radiation [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other IRF4 alterations, most commonly extra copies of IRF4, were seen in a wide variety of T-cell lymphoproliferative disorders, including cutaneous ALCL, and were mutually exclusive with cases harboring IRF4/DUSP22 translocations [10]. The effects of additional cytogenetic alterations on prognosis are unknown; rare cases of DUSP22 rearranged ALCLs demonstrating other alterations, one with concurrent TP63 rearrangement and another with concurrent MYC rearrangement, showed complete remission after chemotherapy although the patient with DUSP22 and MYC rearrangements died 53 months after diagnosis from an unknown cause [8,12]. There is no consensus on the optimal therapy for PCNSL, but treatment most often consists of high-dose methotrexate as part of multiagent chemotherapy, with or without radiation [41].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in TP63 are associated with a poor prognosis and lack of any of these rearrangements with an intermediate prognosis, with 5-year OS of 0–17% and 33–42%, respectively [ 1 , 11 ]. MYC rearrangement has been rarely reported in ALK-negative ALCL with 2 patients recently described by Khanlari et al both of whom had aggressive disease although one demonstrated a concurrent DUSP22 rearrangement and had longer survival compared to the patient without the alteration [ 12 ].…”
Section: Introductionmentioning
confidence: 99%